Kukoamine A activates Akt/GSK-3β signaling pathway to inhibit oxidative stress and relieve myocardial ischemia-reperfusion injury - Xu,Han (2022)
ABSTRACT Purpose: Myocardial ischemia/reperfusion (MI/R) injury refers to a pathological condition of treatment of myocardial infarction. Oxidative stress and inflammation are believed to be important mechanisms mediating MI/R injury. Kukoamine A (KuA), a sperm, is the main bioactive component extracted from the bark of goji berries. In this study, we wanted to investigate the possible effects of KuA on MI/R injury. Methods: In this experiment, all rats were divided into sham operation group, MI/R group, KuA 10 mg + MI/R group, KuA 20 mg + MI/R group. After 120 min of ischemia/reperfusion treatment, left ventricular systolic pressure (LVSP), left ventricular end-diastolic pressure (LVEDP), maximal rates of rising and fall of left ventricular pressure (±dp/dtmax), and ischemic area were detected. Serum samples of rats in each group were collected. The enzyme activities of catalase (CAT), glutathione peroxidase (GSH-PX), superoxide dismutase (SOD), levels of malondialdehyde (MDA), CK muscle/brain (CK-MB), tumor necrosis factor (TNF), interleukin-1β (IL-1β), and interleukin-6 (IL-6) were detected using enzyme-linked immunosorbent assay (ELISA). The apoptosis of myocardium in each group was detected according to the instructions of the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. The expressions of mammalian target of glycogen synthase kinase-3β (GSH-3β) and protein kinase B (Akt) mRNA level in myocardial tissues were detected via reverse transcription-polymerase chain reaction (RT-PCR). Results: MI/R rats showed a significant increase in oxidative stress and inflammation. In addition, we showed that KuA significantly improved the myocardial function such as LVSP, left ventricular ejection fraction, +dp/dt, and -dp/dt. Here, it attenuated dose-dependent histological damage in ischemia-reperfused myocardium, which is associated with the enzyme activities of SOD, GSH-PX, and levels of MDA, IL-6, TNF-α, L-1β. Conclusions: KuA inhibited gene expression of Akt/GSK-3β, inflammation, oxidative stress and improved MR/I injury. Taken together, our results allowed us to better understand the pharmacological activity of KuA against MR/I injury.